Are we losing wetlands faster than we can restore them? - Corrales Chaves, Lenin (2025)
The critical importance of wetland ecosystems is highlighted, as they provide essential services such as regulating the hydrological cycle, flood control, and filtering pollutants. Globally, 64 % of wetlands have been lost since 1970, with Asia being the most affected region. Agricultural expansion, urban development, and aquaculture are some of the main drivers of the degradation of these ecosystems, particularly mangroves, which play a key role in climate change mitigation.  In Costa Rica, wetlands under inventory represent 6.01 % of the national territory, and although the country has made progress in their protection, with 49 % of wetlands falling under some category of protected wild area, challenges remain, such as agricultural expansion, livestock farming, and sedimentation.  At the international level, the Ramsar Convention has been key to wetland conservation efforts, with over 2.57 million km2 protected. However, additional efforts are needed to mitigate the threats to these ecosystems, especially in the context of climate change.